Nato after the Brussels Summit. An optimistic perspective - Garcia, Francisco Miguel Gouveia Pinto Proença (2018)
This paper aims at analyzing the results of the NATO Summit held in Brussels between 11 and 12 July 2018 by focusing on three major subjects, all of which are at the heart of the Alliance's concerns: first, NATO relations with Russia; second, the Alliance's defence and deterrence posture to face challenges and threats, whether on its eastern or southern flank; and finally, NATO relations with the European Union (EU). Following the annexation of Crimea by Russia in 2014, relations with the Alliance and even political dialogue have deteriorated significantly, driving the Alliance to adopt a new defence and deterrence posture. Also, in the South, NATO faces several challenges and threats, having to adapt its defence and deterrence posture to another context. The NATO-EU partnership continues to be strategic for strengthening defence in the European continent but also for cementing transatlantic relations, and it is imperative for the strength of this relationship to fulfill the burden-sharing commitments by increasing the European Allies defence budgets.